Longan extract suppresses food intake through regulation of POMC/AgRP neuronal activities and endoplasmic reticulum stress in hypothalamus of db/db mice - Eo, Hyeyoon; Kim, Seong Hye; Ju, In Gyoung; Huh, Eugene; Kim, Sinyeon; Choi, Jin Gyu; Kim, Se Woong; Son, Miwon; Oh, Myung Sook (Frontiers in Nutrition, 2023)
Type 2 diabetes mellitus (T2DM) is one of the biggest public health issues worldwide and closely related to development of other chronic diseases such as cardiovascular diseases, cancer and neurodegenerative diseases. Considerable percentage of T2DM patients undergo have suffered from binge eating disorder which exacerbates insulin resistance and metabolic challenges. Longan (Dimocarpus longan L.) and its constituents are reported for their various health benefits. However, it is still unknown whether longan fruit supplementation can ameliorate glucose homeostasis and binge eating disorder found in T2DM. The current study aimed to investigate whether longan fruit extract (LE) supplementation can improve diabetic hyperglycemia through modulation of feeding center located in hypothalamus of db/db T2DM mice. As a result, LE supplementation ameliorated fasting blood glucose levels and reduced excessive epididymal fat accumulation. In addition, LE administration improved glucose tolerance and insulin sensitivity in db/db mice. Especially, LE supplemented mice showed less food consumption which was in line with increase of pro-opiomelanocortin (POMC) neuronal activities and decrease of agouti-related peptide (AgRP) neuronal activities. Furthermore, LE supplementation reduced hypothalamic endoplasmic reticulum (ER) stress which was stimulated in db/db mice. As ER stress is a crucial factor involving in appetite control and glucose homeostasis, the effect of LE supplementation on circulating glucose levels and feeding behavior might be mediated by suppression of hypothalamic ER stress. Collectively, these findings suggest that LE could be a potential nutraceutical for improvement of T2DM as well as patients with satiety issues.